Aneka Olahan Minuman Berbahan Dasar Jahe untuk Membantu Menjaga Stamina Tubuh di Masa Pandemi Covid-19 - Sri Harimurti; Rusnani Rusnani; Epit Erwandri; Enita Enita (Jurnal Abdimas ADPI Sains dan Teknologi, 2023)
The lotus village is located in Muara Bulian District, Batang Hari Regency, Jambi Province. During the Covid-19 Pandemic, the people in Teratai Village also felt panic and anxiety. One of the efforts to overcome this epidemic is by continuing to maintain stamina to stay healthy, one of which is by utilizing ginger-based drinks. Ginger contains bioactives that can function as antioxidants with the active ingredient zingeron which is very beneficial for health. This Community Service aims to introduce various processed drinks with ginger-based ingredients, to help foster interest in home-based businesses that use ginger as a base, as well as provide direction regarding the marketing of home business products during a pandemic. The extension method is carried out to introduce to the public about various preparations with the basic ingredients of ginger. Apart from ginger, it turns out that ginger can be made for Andrek drinks, Ronde, sekoteng and many more. Questionnaire results from 21 respondents showed that the people of Teratai Village were in an effort to overcome the Covid-19 pandemic by always maintaining their health. A business that has been passed down from generation to generation and is still being carried out by making ginger based drinks. However, due to the limitations of knowledge and information, the public only knows ginger, which is a ginger-based product.